Understanding how Lewis acids dope organic semiconductors: a "complex" story. Issue 20 (21st April 2021) - Marqués, Pablo Simón; Londi, Giacomo; Yurash, Brett; Nguyen, Thuc-Quyen; Barlow, Stephen; Marder, Seth R.; Beljonne, David
Abstract : Here we report on DFT calculations investigating the mechanistic aspects in doping organic semiconductors by the use of Lewis acids. Our results highlight the role played by the formation of diboron-containing bridged anions in the doping mechanism. Abstract : We report on computational studies of the potential of three borane Lewis acids (LAs) (B(C6 F5 )3 (BCF), BF3, and BBr3 ) to form stable adducts and/or to generate positive polarons with three different semiconducting π-conjugated polymers (PFPT, PCPDTPT and PCPDTBT). Density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations based on range-separated hybrid (RSH) functionals provide insight into changes in the electronic structure and optical properties upon adduct formation between LAs and the two polymers containing pyridine moieties, PFPT and PCPDTPT, unravelling the complex interplay between partial hybridization, charge transfer and changes in the polymer backbone conformation. We then assess the potential of BCF to induce p-doping in PCPDTBT, which does not contain pyridine groups, by computing the energetics of various reaction mechanisms proposed in the literature. We find that reaction of BCF(OH2 ) to form protonated PCPDTBT and [BCF(OH)] −, followed by electron transfer from a pristine to a protonated PCPDTBT chain is highly endergonic, and thus unlikely at low doping concentration. The theoretical and experimental data can, however, be reconciled if one considers the formation of [BCF(OH)BCF] − or [BCF(OH)(OH2 )BCF] − counterions rather than [BCF(OH)] − and invokes subsequent reactions resulting in the elimination of H2 .